Lupine sowings with grain crops grown in the conditions of radioactive pollution - D. M. Sitnov (Зерновое хозяйство России, 2018)
The study was conducted in 2012-2014 in the south-west of the Bryansk region polluted by radiation during the nuclear accident in the Chernobyl NES, so the purpose was not only to obtain highly productive fodder, but also to harvest the products with a normative number of radionuclides. The trial was carried out on sod-podzolic sandy soil with the level of pollution 137Cs to 850 кB/м2. The scheme of the trial included one-type sowings of fodder crops (yellow lupine, oats, ryegrass, Sudan grass and millet) and their combinations. The trials were conducted on the non-fertilized soil and on the soil fertilized with 180 kg of potassium per hectare under various seeding rates of grain component combined with lupine. The yellow lupine showed the largest productivity of grain-haylage mass among one-type sowings (190…214 hwt/ha); in multi-type sowings the combination of yellow lupine with Sudan grass and millet produced 285 and 294 hwt/ha with a maximum seeding rate of grain component on the soil fertilized with potassium. It’s necessary to note that the increased seeding rate of grain component combined with lupine resulted both in the increase of grain-haylage mass and in the decrease of cesium content in fodder. The fertilizing of potassium had no effect on the decrease of cesium in grain-haylage mass of lupine to 400 Bk/kg that proves the necessity to use cesium in the sowings combined with crops having the lowest ability to accumulate radionuclides. The content of 137Cs in grain crops grown in non-fertilized soil was 1.4…2.1 times lower than the permissible level. The increase of grain component in the combinations with lupine gave an opportunity to bring to the norm of cesium content (137), and the fertilizing of 180 kg of potassium per hectare allowed reducing this index in further sowings.